Answer:
(sqrt)x -3=y
Step-by-step explanation:
x=(y+3)^2
=![\sqrt{(y+3)^{2}](https://tex.z-dn.net/?f=%5Csqrt%7B%28y%2B3%29%5E%7B2%7D)
=y+3
-3=y
Answer:
hypotenuse
Step-by-step explanation:
the other sides are known as legs
Answer: f(-2) should be 6
Step-by-step explanation:
Answer:
t = 11.45 years
Step-by-step explanation:
A = p(1+r/n)^nt
A = future value = $12000
P = present value = $6000
n = number of periods = 4
r = interest rate = 6.1% = 0.061
t = number of years = ?
t = log(A/P) / n[log(1 + r/n)]
= log(12000/6000) / 4[log(1+0.061/4)]
= log(2) / 4[log(1 + 0.01525)]
= 0.3010 / 4[log(1.01525)]
= 0.3010 / 4(0.00657)
= 0.3010 / 0.02628
= 11.45 years
Answer:m<b=m<d+125 degrees
Step-by-step explanation: